Electrical detection of spin transport in Si two-dimensional electron gas systems - Chang, Li-Te; Fischer, Inga Anita; Tang, Jianshi; Wang, Chiu-Yen; Yu, Guoqiang; Fan, Yabin; Murata, Koichi; Nie, Tianxiao; Oehme, Michael; Schulze, Jörg; Wang, Kang L. (Nanotechnology, 2016)
Spin transport in a semiconductor-based two-dimensional electron gas (2DEG) system has been attractive in spintronics for more than ten years. The inherent advantages of high-mobility channel and enhanced spin-orbital interaction promise a long spin diffusion length and efficient spin manipulation, which are essential for the application of spintronics devices. However, the difficulty of making high-quality ferromagnetic (FM) contacts to the buried 2DEG channel in the heterostructure systems limits the potential developments in functional devices. In this paper, we experimentally demonstrate electrical detection of spin transport in a high-mobility 2DEG system using FM Mn-germanosilicide (Mn(Si0.7Ge0.3)x) end contacts, which is the first report of spin injection and detection in a 2DEG confined in a Si/SiGe modulation doped quantum well structure (MODQW). The extracted spin diffusion length and lifetime are lsf = 4.5 μm and at 1.9 K respectively. Our results provide a promising approach for spin injection into 2DEG system in the Si-based MODQW, which may lead to innovative spintronic applications such as spin-based transistor, logic, and memory devices.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Mn-doped SiGe; modulation-doped quantum well structure; Si/SiGe; spin injection and detection; spin transport; two-dimensional electron gas